Evaluation of off‐target effects of gapmer antisense oligonucleotides using human cells. (12th November 2019) - Yoshida, Tokuyuki; Naito, Yuki; Yasuhara, Hidenori; Sasaki, Kiyomi; Kawaji, Hideya; Kawai, Jun; Naito, Mikihiko; Okuda, Haruhiro; Obika, Satoshi; Inoue, Takao
Abstract: Antisense oligonucleotide (ASO) has the potential to induce off‐target effects due to complementary binding between the ASO and unintended RNA with a sequence similar to the target RNA. Conventional animal studies cannot be used to assess toxicity induced by off‐target effects because of differences in the genome sequence between humans and other animals. Consequently, the assessment of off‐target effects with in silico analysis using a human RNA database and/or in vitro expression analysis using human cells has been proposed. Our previous study showed that the number of complementary regions of ASOs with mismatches in the human RNA sequences increases dramatically as the number of tolerated mismatches increases. However, to what extent the expression of genes with mismatches is affected by off‐target effects at the cellular level is not clear. In this study, we evaluated off‐target effects of gapmer ASOs, which cleave the target RNA in an RNase H‐dependent manner, by introducing the ASO into human cells and performing microarray analysis. Our data indicate that gapmer ASOs induce off‐target effects depending on the degree of complementarity between the ASO and off‐target candidate genes. Based on our results, we also propose a scheme for the assessment of off‐target effects of gapmer ASOs. Abstract : We showed that gapmer oligonucleotide (ASO) induce off‐target effects depending on the degree of complementarity between the ASO and off‐target candidate genes. Based on our results, we also proposed a scheme for the assessment of off‐target effects of gapmer ASOs.